Microstructural and in vitro characterization of 45S5 bioactive glass coatings deposited by solution precursor plasma spraying (SPPS) - Canas, E.; Orts, M. J.; Boccaccini, Aldo R.; Sanchez, E. (Surface & Coatings Technology, 2019)
The present work focused on the development of bioactive glass coatings employing Solution Precursor Plasma Spraying. Precursors of SiO2, CaO, Na2O and P2O5 were mixed in distilled water to prepare concentrated solutions with a composition close to the 45S5 bioactive glass.
CRIS-Team WoS Importer:2019-07-12